Indústrias criativas: um estudo no setor da gastronomia - Cunha, Marusa Hitaly da Silva (2019)
Based on the conception that food is culture when produced and consumed (MONTANARI, 2008), that the core business of the creative industries resides in the offer of products and services associated with a cultural value (CAVES, 2000), and considering the growing importance of gastronomy in the Brazilian Creative Industry (FIRJAN, 2016), the starting point of this research consisted in the attempt to analyze gastronomy under the theoretical lens of the creative industries. Under this lens, was noticed dualities in the theoretical and practical aspects related to these industries. The very creativity which is the key feature of the creative industries, has two dimensions: an objective/instrumental/rational and other subjective/aesthetic (LEAL, 2007); there is also a duality intrinsic to the creative industries: the tension between the commercial/instrumental/rational instance and the aesthetic/artistic instance (BENDASSOLLI et al., 2009). The present qualitative research, outlined by the progressive paradigm and the postmodernist perspective, was outlined with an exploratory and descriptive purpose, and its general objective was to analyze how are configured the characteristics and dualities of the creative industry in the perception of professionals of the gastronomic creative industry. The strategy adopted was the case study; the primary data were collected through semistructured interviews with eight professionals from the artisanal gastronomic segment. The data collected are treated through the content analysis and operationalized in the software ATLAS.ti. The results indicate that the characteristics of the creative industries are perceived by the professionals of the gastronomic creative industry in a view predominantly associated with aspects and elements of subjective/aesthetic order and to the post-bureaucratic organizational aproaches. The results also indicate that the main dualities perceived and experienced by professionals are those that involve tensions between the local and the global, between authenticity and success, between commercial instance and the aesthetic/artistic instance, and between genuine and imitation.